2022
DOI: 10.3390/cancers14112763
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistant Cancer Cell Lines Are Characterized by Migratory, Amino Acid Metabolism, Protein Catabolism and IFN1 Signalling Perturbations

Abstract: Chemoresistance remains the major barrier to effective ovarian cancer treatment. The molecular features and associated biological functions of this phenotype remain poorly understood. We developed carboplatin-resistant cell line models using OVCAR5 and CaOV3 cell lines with the aim of identifying chemoresistance-specific molecular features. Chemotaxis and CAM invasion assays revealed enhanced migratory and invasive potential in OVCAR5-resistant, compared to parental cell lines. Mass spectrometry analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…Interestingly, the positive expression profiling of TGFBI with important ECM remodeling proteins such as GFPT2, FLNA, G6PD, ITGAV, ITGA1 and ITGA2 shown by TIMER datasets suggest a potential role of these proteins in remodeling ECM in response to carboplatin treatment. Consistent with our findings, a recent study has shown increased migratory, amino acid metabolism, protein catabolism and IFN1 signaling perturbation in platinum resistant ovarian cancer cell lines [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the positive expression profiling of TGFBI with important ECM remodeling proteins such as GFPT2, FLNA, G6PD, ITGAV, ITGA1 and ITGA2 shown by TIMER datasets suggest a potential role of these proteins in remodeling ECM in response to carboplatin treatment. Consistent with our findings, a recent study has shown increased migratory, amino acid metabolism, protein catabolism and IFN1 signaling perturbation in platinum resistant ovarian cancer cell lines [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…OVCAR-5, the human ovarian cancer cell line, was obtained from Dr. Thomas Hamilton (Fox Chase Cancer Centre, Philadelphia, PA) and cultured under similar conditions to those previously described by us [ 17 , 22 ]. Briefly, the carboplatin-resistant (CBPR) OVCAR-5 cells were obtained by treating parental OVCAR-5 cells with 25 µM of carboplatin for 24 h. (Hospira Australia Pty Ltd., Mulgrave, Australia) followed by 72 h of recovery phase.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we have generated carboplatin-resistant cancer cell lines (OVCAR-5 and CaOV3). Label-free proteomics analysis on these two pairs of parental and carboplatin-resistant cell lines showed a shared dysregulation of cytokine and type 1 interferon signaling, potentially revealing a common molecular feature of chemoresistance [ 17 ]. Here, we aimed to identify protein markers of chemotherapy response in HGSOC patients who did not respond to platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study analyzing the metabolome and proteome in normal and resistant group OC cells revealed perturbations of IFN signaling in resistant group cancer cells. Tyrosine kinase 2 (TYK2), an enzyme that plays a key role in IFN-I signaling, was reduced in abundance in CAOV3 CBPR cells ( 89 ). This conclusion was similarly validated by clinical data showing that patients with high IFN-γ in the immune microenvironment had a better prognosis in platinum-treated patients ( 90 ).…”
Section: The Roles Of Interferons In Oc Treatmentmentioning
confidence: 99%